Analisis Yuridis Terhadap Penerapan Hukum Acara PTUN Dalam Putusan Nomor : 20/G/2020/PTUN-JKT - Wardhana, Adi Pratomo Kusuma (Peneliti.net, 2025)
The existence of state administrative courts in various modern countries, especially Welfare State countries, is a milestone on which the hopes of the community or people are based to defend their material and immaterial interests or rights which are harmed by the actions of government agencies or officials due to government decisions. Which written or unwritten and/or factual acts of government administration carried out. The purpose of establishing a state administrative court is to provide legal protection for the people against actions by government agencies or officials that violate the law or human rights in the field of state administrative law. Apart from that, the state administrative court will also provide the same legal protection to government agencies or officials who act correctly and in accordance with applicable law.